A low-cost high-capacity TiZrMnCrCe hydrogen storage alloy and a preparation method thereof
Patent Information
- Application Number
- CN202611400098.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]1、由于合金中的Ti元素偏析,合金的吸放氢容量通常低于1.70 wt.%,距TiMn2基储氢合金的理论容量2.00 wt.%有一定的差距;
[0018]经XRD检测可知,引入原子半径较大的Ce元素后合金主相仍为TiMn2相,第二相为CeO2相、β-Ti相,其中,β-Ti相含量随着Ce含量的增加逐渐降低;同时主相晶胞体积增加,具体为,x从0.3增加到0.5,合金晶格常数a由4.8606 Å增加至4.8703Å,c由7.9717 Å增加至7.9872Å,c/a由1.6401降至1.6398然后提升到1.6400,相应地,晶胞体积由163.8513 Å3增加至164.8258Å3。
Smart Images

Figure CN123005201A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid-state hydrogen storage materials technology, specifically a low-cost, high-capacity TiZrMnCrCe hydrogen storage alloy and its preparation method. Background Technology
[0002] Solid-state hydrogen storage offers advantages such as high hydrogen storage density and high safety. Among these, TiZrMnCr hydrogen storage alloys belong to the AB2-type Laves phase hydrogen storage alloy system, exhibiting good cycle stability, low hysteresis coefficient, and low cost. However, two issues remain for the large-scale application of TiZrMnCr hydrogen storage alloys:
[0003] 1. Due to the segregation of Ti in the alloy, the hydrogen absorption and desorption capacity of the alloy is usually less than 1.70 wt.%, which is quite different from the theoretical capacity of 2.00 wt.% of TiMn2-based hydrogen storage alloy;
[0004] 2. Because a dense oxide layer forms on the surface of the alloy when it comes into contact with air, it usually needs to be activated by multiple cycles under high temperature and high pressure conditions, which increases the cost of use and reduces the efficiency of use.
[0005] To address the aforementioned issues, Cr and Zr can be used to partially replace Ti in TiZrMnCr alloys, thereby improving the alloy's hydrogen storage capacity and activation performance. Existing literature 1 (Zhu XM, Yan Z, Liu ZP, et al. Effects of Zr–Cr co-substitution for Ti on the microstructure and hydrogen storage properties of TiMn2-based alloys[J]. Materials Science and Engineering, 323(B):118849, 2026) prepared Ti... 0.92-x Zr 0.08 (Zr) 0.55 Cr 0.45 ) x Mn 0.7 Cr 1.1 The alloy, where x = 0, 0.02, 0.04, is formed by partially substituting Ti with Zr and Cr. When x = 0.04, the alloy exhibits the best performance, with the activation energy decreasing from 32.3 kJ / mol to 25.9 kJ / mol. It can be fully activated by the first hydrogen absorption and desorption under the conditions of 303 K and 3 MPa, but its hydrogen storage capacity is only 1.70 wt.%.
[0006] For example, other metallic elements can be used to partially replace Ti or Mn in TiZrMnCr alloys to improve the hydrogen storage capacity and activation performance of the alloy. Existing literature 2 (Zhou PP, Cao ZM, et al. Study on low-vanadium Ti-Zr-Mn-Cr-V based alloys for high-density hydrogen storage[J]. International Journal of Minerals, Metallurgy and Materials, 47(3): 1710-1722, 2022) prepared Ti by partially replacing Mn with V. 0.93 Zr 0.07 Mn 1.1+y Cr 0.7+z V 0.2-y-z Ti 0.93+ w Zr 0.07 Mn 1.15 Cr 0.7 V 0.15 Various multi-element alloys are included, where y = 0, 0.05; z = 0, 0.02, 0.05; w = 0, 0.02, 0.04. Ti is one of the alloys in this case. 0.95 Zr 0.07 Mn 1.15 Cr 0.7 V 0.15 The alloy exhibits the best overall performance, with a hydrogen absorption capacity of 1.83 wt.% at 283 K. However, the hydrogen absorption and desorption plateaus of this alloy are significantly lagging and tilted, resulting in a low effective hydrogen desorption capacity within the commonly used pressure range. Furthermore, the high market price of metallic V significantly increases the cost of the alloy.
[0007] Furthermore, the addition of rare earth elements to TiZrMnCr alloys can lead to surface segregation, and rare earth elements can combine with hydrogen to form rare earth hydrides, significantly improving the activation performance of the alloy. Existing literature 3 (Zhou WJ, Li TY, Zhang AJ, et al. Effect of Ce element on hydrogen storage property of TiMn2-based alloys[J]. International Journal of Minerals, Metallurgy and Materials,33(3): 971-979, 2026) introduces the rare earth element Ce to prepare Ti... 0.98 Zr 0.02 Mn 1.5 Cr0.05 V 0.43 Fe 0.09 Ce x Alloys were prepared with x = 0, 0.02, 0.04, and 0.06. Results showed that the addition of rare earth element Ce refined the alloy grains, and the formation of the CeO2 phase increased the interfacial area, promoting hydrogen atom diffusion and thus improving activation performance and reducing the hysteresis of the hydrogen absorption / desorption plateau. The alloy was fully activated after two activations at 293 K and 4 MPa. The alloy exhibited the highest hydrogen storage capacity (1.85 wt.%) at x = 0.04. However, the high V content resulted in a higher alloy cost.
[0008] For example, existing literature 4 (Zhou L, Li WX, Hu HZ, et al. Ce-Doped TiZrCrMnloys for enhanced hydrogen storage[J]. Energy & Fuels, 36(7): 3997–4005,2022) added Ce to TiZrMnCr alloy to prepare Ti 0.8 Zr 0.2 Cr 0.75 Mn 1.25 Ce x An alloy was prepared, where x = 0, 0.01, 0.02, 0.03, and 0.04. The results showed that the main phase of the alloy remained TiMn2 after the addition of Ce, and the CeO2 second phase suppressed Ti element segregation, resulting in a more uniform alloy composition distribution. At x = 0.02, the alloy exhibited the best activation performance and hydrogen absorption capacity, requiring only one activation treatment at 298 K and 10 MPa for complete activation. At 298 K, the hydrogen absorption capacity was 1.98 wt.%, but the hydrogen release capacity was only 1.79 wt.%, leaving a residual hydrogen content of 0.19 wt.%. This alloy demonstrated excellent activation performance and hydrogen absorption capacity, but its high residual hydrogen content and unsatisfactory reversible hydrogen release capacity were not ideal. Summary of the Invention
[0009] The purpose of this invention is to provide a low-cost, high-capacity TiZrMnCrCe hydrogen storage alloy and its preparation method. The technical principle of this invention is as follows: the hydrogen storage capacity of a hydrogen storage alloy is closely related to the uniformity of its composition and microstructure, while its activation performance is closely related to the size of the interatomic gaps and the hydrogen atom diffusion channels. Since the rare earth element Ce, with its large atomic radius, can suppress the segregation of Ti, adding a higher content of Ce to the alloy suppresses Ti segregation, improves the uniformity of the alloy composition and microstructure, and thus increases the alloy's hydrogen storage capacity. Adding Ce increases the cell volume, increases the interatomic gaps, increases the content of the CeO2 second phase, increases the number of grain boundaries, increases the hydrogen atom diffusion channels, and reduces the hydrogen atom diffusion resistance, thereby effectively improving the alloy's activation performance.
[0010] To achieve the above objectives, the present invention adopts the following technical solution:
[0011] A TiZrMnCrCe hydrogen storage alloy with the general formula Ti 0.88 Zr 0.22 Mn 1+x Cr 0.5+x Ce x Where x = 0.3-0.5, the atomic ratio of each element in the general formula is Ti:Zr:Mn:Cr:Ce = 0.88:0.22:(1+x):(0.5+x):x; the main phase of the hydrogen storage alloy is TiMn2 phase. The lattice constant of the main phase is 4.8606-4.8703 Å, c is 7.9717-7.9872 Å, c / a is 1.6398-1.6401, and the cell volume is 163.8513-164.8258 Å. 3 ;
[0012] A method for preparing a TiZrMnCrCe hydrogen storage alloy includes the following steps: First, pure titanium blocks, pure zirconium blocks, pure manganese blocks, pure chromium blocks and pure cerium blocks are weighed according to mass percentage and placed in a crucible. After vacuuming, the alloy is melted under argon conditions to obtain a uniform alloy ingot. The alloy ingot is mechanically crushed to obtain alloy particles, which are then activated before the first hydrogen absorption and desorption.
[0013] The alloy composition by mass percentage is as follows: Ti 15.80-19.39 wt.%; Zr 7.53-9.24 wt.%; Mn 30.91-32.88 wt.%; Cr 19.15-19.50 wt.%; Ce 19.35-26.27 wt.%.
[0014] The vacuum melting conditions are as follows: a low-melting-point pure cerium block is placed above other metal raw materials, the vacuum degree ranges from 0.005 to 10.0 Pa, the argon pressure is 0.02 to 0.06 MPa, and the melting time is 3 to 10 min.
[0015] The activation conditions are as follows: the activation temperature is 318 K, the hydrogen pressure is 10 MPa and maintained for 1.0 h, then the temperature is lowered to 298 K and hydrogen is absorbed for 1.0 h, and then the hydrogen is released by vacuuming to complete one activation treatment; the activation treatment is performed once.
[0016] The obtained hydrogen storage alloy exhibits the following characteristics within a hydrogen absorption / desorption temperature range of 273-293 K: hydrogen absorption capacity of 1.74-1.96 wt.% and hydrogen desorption capacity of 1.66-1.86 wt.%; hydrogen absorption plateau pressure of 0.48-1.46 MPa and hydrogen desorption plateau pressure of 0.30-1.09 MPa; hydrogen absorption activation energy of 11.5-14.8 kJ / mol and hydrogen desorption activation energy of 23.2-25.5 kJ / mol.
[0017] The present invention has been tested and the following technical effects have been obtained:
[0018] XRD analysis revealed that after introducing Ce, an element with a large atomic radius, the main phase of the alloy remained TiMn2, with CeO2 and β-Ti phases as secondary phases. The β-Ti phase content gradually decreased with increasing Ce content. Simultaneously, the cell volume of the main phase increased; specifically, as x increased from 0.3 to 0.5, the alloy lattice constant a increased from 4.8606 Å to 4.8703 Å, c increased from 7.9717 Å to 7.9872 Å, and c / a decreased from 1.6401 to 1.6398 and then increased to 1.6400. Correspondingly, the cell volume increased from 163.8513 Å. 3 Increased to 164.8258 Å 3 .
[0019] PCT testing showed that, at a hydrogen absorption / desorption temperature of 273 K, when x=0.3, the alloy's hydrogen absorption capacity was 1.91 wt.%, its hydrogen desorption capacity was 1.79 wt.%, its hydrogen absorption activation energy was 13.7 kJ / mol, and its hydrogen desorption activation energy was 23.9 kJ / mol; when x=0.4, the alloy's hydrogen absorption capacity was 1.96 wt.%, its hydrogen desorption capacity was 1.86 wt.%, its hydrogen absorption activation energy was 11.5 kJ / mol, and its hydrogen desorption activation energy was 23.2 kJ / mol; and when x=0.5, the alloy's hydrogen absorption capacity was 1.94 wt.%, its hydrogen desorption capacity was 1.85 wt.%, its hydrogen absorption activation energy was 14.8 kJ / mol, and its hydrogen desorption activation energy was 25.5 kJ / mol.
[0020] Therefore, performance tests show that the present invention has the following advantages compared with the prior art:
[0021] 1. Adding a high content of rare earth element Ce to the alloy significantly inhibits the segregation of Ti element, improves the uniformity of alloy composition and microstructure, and thus improves the hydrogen storage capacity of the alloy.
[0022] 2. The addition of Ce, an element with a large atomic radius, increases the cell volume, increases the interatomic spacing, increases the content of CeO2 second phase, increases the number of grain boundaries, increases the hydrogen atom diffusion channels, and reduces the hydrogen atom diffusion resistance, thereby effectively improving the activation performance of the alloy.
[0023] 3. The addition of low-cost Ce element reduces the cost of TiZrMnCr hydrogen storage alloy. Attached Figure Description
[0024] Figure 1 The XRD patterns of the hydrogen storage alloys of Example 1, Comparative Example 1, Example 2 and Example 3 are shown below; Figure 2 Ti prepared in Example 1 0.88 Zr 0.22 Mn 1.4 Cr 0.9 Ce 0.4 PCT curve; Figure 3 Ti prepared for Comparative Example 1 0.88 Zr 0.22 Mn1Cr 0.5 PCT curve; Figure 4 Ti prepared in Example 2 0.88 Zr 0.22 Mn 1.3 Cr 0.8 Ce 0.3 PCT curve; Figure 5 Ti prepared in Example 3 0.88 Zr 0.22 Mn 1.5 Cr1Ce 0.5 The PCT curve. Detailed Implementation
[0025] Based on the above component design, the comparative examples and embodiments of the present invention are as follows:
[0026] Comparative Example 1: Ti 0.88 Zr 0.22 Mn1Cr 0.5 ;
[0027] Example 1: Ti 0.88 Zr0.22 Mn 1.4 Cr 0.9 Ce 0.4 ;
[0028] Example 2: Ti 0.88 Zr 0.22 Mn 1.3 Cr 0.8 Ce 0.3 ;
[0029] Example 3: Ti 0.88 Zr 0.22 Mn 1.5 Cr1Ce 0.5 ;
[0030] The present invention will be further described in detail through embodiments and with reference to the accompanying drawings, but this is not intended to limit the scope of the invention.
[0031] Example 1
[0032] Ti 0.88 Zr 0.22 Mn 1.4 Cr 0.9 Ce 0.4 The preparation method of the alloy includes the following steps: First, pure titanium blocks, pure zirconium blocks, pure manganese blocks, pure chromium blocks and pure cerium blocks are weighed according to the mass percentage and placed in a crucible. After vacuuming, the alloy is melted under argon conditions to obtain a uniform alloy ingot. The alloy ingot is mechanically crushed to obtain alloy particles, which are then activated before the first hydrogen absorption and desorption.
[0033] The alloy composition by mass percentage is as follows: Ti 17.41 wt.%; Zr 8.29 wt.%; Mn 31.79 wt.%; Cr 19.34 wt.%; Ce 23.16 wt.%.
[0034] The vacuum melting conditions are as follows: a low-melting-point pure cerium block is placed above other metal raw materials, the vacuum degree is 0.5 Pa, the argon pressure is 0.04 MPa, and the melting time is 5 min.
[0035] The activation conditions are as follows: maintaining the activation temperature at 318 K and the hydrogen pressure at 10 MPa for 1.0 h, cooling to 298 K and absorbing hydrogen for 1.0 h, and then releasing hydrogen by evacuation to complete one activation treatment; the activation treatment is performed once.
[0036] To demonstrate the phase composition and crystal characteristics of the alloy in Example 1, XRD tests were performed. The test results are as follows: Figure 1As shown in Table 1, a is 4.8678 Å, c is 7.9820 Å, c / a is 1.6398, and the cell volume is 164.5494 Å. 3 The main phase of the alloy is TiMn2 phase, and the secondary phases are CeO2 phase and β-Ti phase.
[0037] Table 1 Summary of Alloy Lattice Constants Obtained from Examples and Comparative Examples
[0038]
[0039] To obtain the hydrogen storage performance of the alloy in Example 1, a PCT test was performed. The test results are as follows: Figure 2 As shown in Table 2, the hydrogen absorption and desorption temperature is 273 K, the hydrogen absorption plateau pressure is 0.64 MPa, and the hydrogen absorption capacity is 1.96 wt.%; the hydrogen desorption plateau pressure is 0.30 MPa, and the hydrogen desorption capacity is 1.86 wt.%.
[0040] The activation energies of the alloy in Example 1 were calculated using the Johnson-Mehl-Avrami model, with the hydrogen absorption activation energy being 11.5 kJ / mol and the hydrogen release activation energy being 23.2 kJ / mol.
[0041] Table 2 Summary of hydrogen storage performance of the alloy in Example 1 under different hydrogen absorption and desorption temperatures
[0042]
[0043] To demonstrate the effect of introducing Ce, a comparative example 1 without Ce is provided.
[0044] Comparative Example 1
[0045] Ti 0.88 Zr 0.22 Mn1Cr 0.5 The preparation method of the alloy, unless otherwise specified, is the same as in Example 1, except that: no metallic Ce is added. The specific alloy composition by mass percentage is as follows: Ti content 29.43 wt.%; Zr content 14.02 wt.%; Mn content 38.38 wt.%; Cr content 18.16 wt.%.
[0046] To demonstrate the phase composition and crystal characteristics of the alloy in Comparative Example 1, XRD tests were performed. The test results are as follows: Figure 1 As shown in Table 1, a is 4.8595 Å, c is 7.9698 Å, c / a is 1.6400, and the cell volume is 163.7381 Å. 3 The main phase of the alloy is TiMn2 phase, and the second phase is β-Ti phase.
[0047] To obtain the hydrogen storage performance of the alloy in Comparative Example 1, PCT testing was performed. The test results are as follows: Figure 3 As shown in Table 3, under the condition of hydrogen absorption and desorption temperature of 273 K, the hydrogen absorption plateau pressure of the alloy is 1.19 MPa and the hydrogen absorption capacity is 1.76 wt.%; the hydrogen desorption plateau pressure is 0.71 MPa and the hydrogen desorption capacity is 1.58 wt.%.
[0048] The activation energies of the alloy in Comparative Example 1 were calculated using the Johnson-Mehl-Avrami model, with hydrogen absorption activation energy of 15.9 kJ / mol and hydrogen release activation energy of 26.7 kJ / mol.
[0049] Table 3 Summary of hydrogen storage performance of alloy in Comparative Example 1 under different hydrogen absorption and desorption temperatures
[0050]
[0051] To demonstrate the effect of Ce addition, Examples 2 and 3 are provided with Ce atomic ratios of 0.3 and 0.5, respectively.
[0052] Example 2
[0053] Ti 0.88 Zr 0.22 Mn 1.3 Cr 0.8 Ce 0.3 The preparation method of the alloy is the same as that of the alloy in Example 1 unless otherwise specified. The difference is that the specific alloy composition by mass percentage is as follows: Ti content 19.39 wt.%; Zr content 9.24 wt.%; Mn content 32.88 wt.%; Cr content 19.15 wt.%; Ce content 19.35 wt.%.
[0054] To demonstrate the phase composition and crystal characteristics of the alloy in Example 2, XRD tests were performed. The test results are as follows: Figure 1 As shown in Table 1, a is 4.8606 Å, c is 7.9717 Å, c / a is 1.6401, and the cell volume is 163.8513 Å. 3 The main phase of the alloy is TiMn2 phase, and the secondary phases are CeO2 phase and β-Ti phase.
[0055] To obtain the hydrogen storage performance of the alloy in Example 2, a PCT test was performed. The test results are as follows: Figure 4 As shown in Table 4, under the condition of hydrogen absorption and desorption temperature of 273 K, the hydrogen absorption plateau pressure of the alloy is 0.54 MPa and the hydrogen absorption capacity is 1.91 wt.%; the hydrogen desorption plateau pressure is 0.35 MPa and the hydrogen desorption capacity is 1.79 wt.%.
[0056] The activation energies of the alloy in Example 2 were calculated using the Johnson-Mehl-Avrami model, with hydrogen absorption activation energy of 13.7 kJ / mol and hydrogen release activation energy of 23.9 kJ / mol.
[0057] Table 4. Summary of hydrogen storage performance of the alloy in Example 2 under different hydrogen absorption and desorption temperatures.
[0058]
[0059] Example 3
[0060] Ti 0.88 Zr 0.22 Mn 1.5 Cr1Ce 0.5 The preparation method of the alloy is the same as that of the alloy in Example 1 unless otherwise specified. The difference is that the specific alloy composition by mass percentage is as follows: Ti content 15.80 wt.%; Zr content 7.53 wt.%; Mn content 30.91 wt.%; Cr content 19.50 wt.%; Ce content 26.27 wt.%.
[0061] To demonstrate the phase composition and crystal characteristics of the alloy in Example 3, XRD tests were performed. The test results are as follows: Figure 1 As shown in Table 1, a is 4.8703 Å, c is 7.9872 Å, c / a is 1.6400, and the cell volume is 164.8258 Å. 3 The main phase of the alloy is TiMn2 phase, the second phase is CeO2 phase, and there is no β-Ti phase. Compared with Comparative Example 1, the content of β-Ti phase decreases with the addition of Ce. When x=0.5, the β-Ti phase disappears. The addition of Ce eliminates the segregation of Ti element.
[0062] Test results are as follows Figure 5 As shown in Table 5, under the condition of hydrogen absorption and desorption temperature of 273 K, the hydrogen absorption plateau pressure of the alloy is 0.48 MPa and the hydrogen absorption capacity is 1.94 wt.%; the hydrogen desorption plateau pressure is 0.33 MPa and the hydrogen desorption capacity is 1.85 wt.%.
[0063] The activation energies of the alloy in Example 3 were calculated using the Johnson-Mehl-Avrami model, with hydrogen absorption activation energy of 14.8 kJ / mol and hydrogen release activation energy of 25.5 kJ / mol.
[0064] Table 5. Summary of hydrogen storage performance of the alloy in Example 3 under different hydrogen absorption and desorption temperatures.
[0065] .
Claims
1. A TiZrMnCrCe hydrogen storage alloy, characterized in that: The general formula of the component is Ti 0.88 Zr 0.22 Mn 1+x Cr 0.5+x Ce x Where x = 0.3-0.5, the atomic ratio of each element in the general formula is Ti:Zr:Mn:Cr:Ce = 0.88:0.22:(1+x):(0.5+x):x; The main phase of the hydrogen storage alloy is the TiMn2 phase.
2. The hydrogen storage alloy according to claim 1, characterized in that: The lattice constants of the main phase of the hydrogen storage alloy are α = 4.8606–4.8703 Å, c = 7.9717–7.9872 Å, c / α = 1.6398–1.6401, and the cell volume is 163.8513–164.8258 Å. 3 .
3. A method for preparing a TiZrMnCrCe hydrogen storage alloy, characterized in that... Includes the following steps: Pure titanium blocks, pure zirconium blocks, pure manganese blocks, pure chromium blocks, and pure cerium blocks are weighed according to their mass percentages and placed in a crucible. After vacuuming, the mixture is melted under argon conditions to obtain a uniform alloy ingot. The resulting alloy ingot is mechanically crushed to obtain alloy particles, which are then activated before the first hydrogen absorption and desorption. The alloy composition by mass percentage is as follows: Ti content 15.80-19.39 wt.%; Zr content 7.53-9.24 wt.%; Mn content 30.91-32.88 wt.%; Cr content 19.15-19.50 wt.%; Ce content 19.35-26.27 wt.%.
4. The preparation method according to claim 3, characterized in that: The vacuum melting conditions are as follows: a low-melting-point pure cerium block is placed above other metal raw materials, the vacuum degree ranges from 0.005 to 10.0 Pa, the argon pressure is 0.02 to 0.06 MPa, and the melting time is 3 to 10 min.
5. The preparation method according to claim 3, characterized in that: The activation conditions are as follows: the activation temperature is 318K, the hydrogen pressure is 10 MPa and maintained for 1.0 h, the temperature is reduced to 298 K and hydrogen is absorbed for 1.0 h, and then the hydrogen is released by vacuuming to complete one activation treatment; the activation treatment is performed once.
6. The preparation method according to claim 3, characterized in that: The obtained hydrogen storage alloy exhibits a hydrogen absorption capacity of 1.74-1.96 wt.% and a hydrogen release capacity of 1.66-1.86 wt.% within a hydrogen absorption / desorption temperature range of 273-293 K; the hydrogen absorption plateau pressure is 0.48-1.46 MPa, and the hydrogen release plateau pressure is 0.30-1.09 MPa.
7. The preparation method according to claim 3, characterized in that: The hydrogen storage alloy has a hydrogen absorption activation energy of 11.5-14.8 kJ / mol and a hydrogen release activation energy of 23.2-25.5 kJ / mol.
